Production of congopain, the major cysteine protease of Trypanosoma (Nannomonas) congolense, in Pichia pastoris reveals unexpected dimerization at physiological Ph - Boulange, A.F.; Khamadi, S.A.; Pillay, D.; Coetzer, T.H.T.; Authié, Edith (Elsevier, 2011)
African animal trypanosomosis (nagana) is arguably the most important parasitic disease affecting livestock in sub-Saharan Africa. Since none of the existing control measures are entirely satisfactory, vaccine development is being actively pursued. However, due to antigenic variation, the quest for a conventional vaccine has proven elusive. As a result, we have sought an alternative ‘anti-disease vaccine approach’, based on congopain, a cysteine protease of Trypanosoma congolense, which was shown to have pathogenic effects in vivo. Congopain was initially expressed as a recombinant protein in bacterial and baculovirus expression systems, but both the folding and yield obtained proved inadequate. Hence alternative expression systems were investigated, amongst which Pichia pastoris proved to be the most suitable. We report here the expression of full length, and C-terminal domain-truncated congopain in the methylotrophic yeast P. pastoris. Differences in yield were observed between full length and truncated proteins, the full length producing 2 to 4 mg of protein per litre of culture, while the truncated form produced 20 to 30 mg/l. The protease was produced as a proenzyme, but underwent spontaneous activation when acidified (pH< 5). To investigate whether this activation was due to autolysis, we produced an inactive mutant (active site Cys→Ala) by site-directed mutagenesis. The mutant form was produced at a much higher rate, up to 100 mg/l culture, as a proenzyme. It did not undergo spontaneous cleavage of the propeptide when subjected to acidic pH suggesting an autocatalytic process of activation for congopain. These recombinant proteins displayed a very unusual feature for cathepsin L-like proteinases, i.e. complete dimerisation at pH > 6, and by reversibly monomerising at acidic pH < 5. This attribute is of utmost importance in the context of an anti-disease vaccine, given that the epitopes recognised by the sera of trypanosome-infected trypanotolerant cattle appear dimer-specific.